A Frontal Ablation Dataset for 49 Tidewater Glaciers in Greenland - Dominik Fahrner; Donald A. Slater; Aman KC; Claudia Cenedese; David A. Sutherland; Ellyn Enderlin; M. Femke de Jong; Kristian K. Kjeldsen; Michael Wood; Peter Nienow; Sophie Nowicki; Till J. W. Wagner (Scientific Data)
Abstract Frontal ablation at tidewater glaciers, which comprises iceberg calving and submarine and subaerial melting, is a key boundary condition for numerical ice sheet models but remains difficult to measure in-situ. Although previous studies have provided frontal ablation estimates over a range of spatiotemporal scales, most use ice discharge as an approximation, thereby neglecting the influence of terminus position change. Here, we present a dataset of frontal ablation estimates for 49 tidewater glaciers in Greenland that have reliable near-terminus bathymetry data. Near-terminus volume change over the period 1987–2020 is determined using previously published datasets of terminus positions (TermPicks) together with ice thicknesses estimated from ArcticDEM, AeroDEM, and Bedmachine v5 bed topography. Assuming a vertical terminus geometry and uniform ice density, we estimate frontal ablation as the residual between mass flux towards the terminus taken from a published dataset and mass change due to changes in terminus position. The frontal ablation dataset offers opportunities for developing new insights into ice dynamics, including helping to improve numerical model hindcasting and projections.